ENVIRONMENTAL, SOCIAL, AND GOVERNANCE DISCLOSURE AND BANK FINANCIAL PERFORMANCE IN INDONESIA: THE MODERATING ROLE OF FIRM SIZE (2020–2024) - Ekklesia Evanggelion; Luluk Tri Harinie; Evinalia Yeba; Meylinda Sukmani (Journal of Management Small and Medium Enterprises (SMEs), 2026)
This study examines whether Environmental, Social, and Governance (ESG) disclosure is associated with the financial performance of Indonesian listed banks during the 2020–2024 period and whether firm size moderates this relationship. The research adopts a quantitative explanatory approach, where ESG disclosure is measured using a disclosure index developed through content analysis of annual and sustainability reports. Financial performance is represented by several indicators, including return on assets, return on equity, net profit margin, and earnings per share. The findings indicate that the direct effects of individual ESG disclosure dimensions on financial performance are generally weak and not consistently evident across different performance indicators. Meanwhile, firm size shows a more stable relationship with financial performance in several model specifications. When the moderating effect is considered, the relationship between ESG disclosure and financial performance appears more conditional, suggesting that the financial relevance of ESG practices may depend on specific bank characteristics. This study is limited by a relatively small sample size and the use of disclosure-based ESG measurement. Future research is recommended to expand the sample coverage, extend the observation period, and incorporate alternative ESG measurement approaches to provide more comprehensive insights into the relationship between ESG practices and financial performance. Keywords: ESG Disclosure; Banking Sector; Financial Performance; Firm Size Moderation; Indonesia Stock Exchange